Sumbangan All-Trans Asam Retinoat (ATRA) Bagi Penyembuhan Periodontitis - Praptiwi Praptiwi; Siti Fatimah Muis; Soeharyo Hadisaputro; Suryono Suryono (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTAll-trans retinoic acid (ATRA) contribution to periodontitis healingBackground: In inflammation and infection of periodontal ligament i.e periodontitis, collagen fiber is damaged. All-trans retinoic acid (ATRA), metabolite of vitamin A, has potency to depress damage in inflammation. Indonesia with high vitamin A deficiency, facing to delayed recovery of periodontitis. The disease is vastly suffered by common people in this country. The study aimed to know the collagen status of periodontal ligament suffering periodontitis treated with tetracycline and ATRA supplementation.Method: The experimental study using post test only design in 12 adult male Wistar rat was done in 7 days. The animal study were induced periodontitis through Porphyromonas gingivalis inoculation. Tetracycline 90 mg/kg was given, beside ATRA supplementation of 10 mg/kg and 5 mg/kg. Four experimental groups were chosen randomly. Group of periodontitis + tetracycline was the control of the study. The independent variables were ATRA supplementation of those high and low dose. The dependent variable was collagen status. Collagen status consist of degradation and synthesis of collagen, indicated by mRNA MMP-2 and mRNA P1CP respectively. They were measured by reversed transcriptase polymerizing chain reaction and thin layer chromatography. All-trans retinoic acid concentration was measured using high performance liquid chromatography. The dataanalyzed using t-test, Oneway ANOVA, post hoc duncan and least significant differences.Result: In group receiving 10 mg ATRA/kgBB, the ATRA level was highest but the collagen degradation was lower although not significant compared to the low dose ATRA group. In both groups the degradation was significantly lower than the control group (p=0.007). The synthesis of collagen in the low dose ATRA group was higher than the high dose ATRA group and the control group.Conclusion: High dose of ATRA supplementation contribution to less degradation of collagen, but in term of collagen synthesis, low dose ATRA supplementation gives better result.Keywords: ATRA supplementation, collagen degradation, periodontitis ABSTRAKLatar belakang: Pada peradangan dan infeksi kronik ligamentum periodontal yaitu periodontitis, terjadi kerusakan serat kolagen. All-trans asam retinoat (ATRA), metabolit vitamin A, berpotensi menekan kerusakan pada peradangan. Tingginya defisiensi vitamin A di Indonesia, menghambat proses penyembuhan periodontitis yang banyak diderita masyarakat luas. Penelitian bertujuan mengetahui status kolagen ligamentum periodontal periodontitis yang mendapat pengobatan tetrasiklin dan suplementasi ATRA.Metode: Studi eksperimental dengan rancangan post test only pada 12 tikus Wistar jantan dewasa telah dilakukan selama 7 hari. Hewan coba diinduksi periodontitis melalui inokulasi bakteri Porphyromonas gingivalis. Diberikan tetrasiklin 90 mg/kg, juga suplementasi ATRA 10 mg/kg dan 5 mg/kg. Empat kelompok studi dipilih secara acak. Kontrol adalah kelompok sakit + tetrasiklin. Variabel bebas adalah suplementasi ATRA dosis tinggi dan dosis rendah, variabel tergantung adalah status kolagen. Status kolagenmencakup degradasi dan sintesis, berturut-turut dengan petanda mRNA MMP-2 dan mRNA P1CP, diukur menggunakan reverse transcriptase polymerizing chain reaction dan thin layer chromatography. Kadar ATRA diukur dengan high performance liquid chromatography. Data dianalisis dengan uji t, Oneway ANOVA, post hoc Duncan dan least significant differences.Hasil: Pada kelompok yang menerima suplementasi ATRA 10 mg/kgBB kadar ATRA tertinggi, tetapi degradasi kolagennya lebih rendah walau tidak bermakna. Kedua kelompok sumplementasi degradasi kolagennya lebih rendah secara bermakna dibanding kelompok kontrol (p=0,007), dalam sintesis kolagen,kelompok yang mendapat suplementasi ATRA 50 mg/kgBB sintesisnya lebih baik dibanding kelompok yang mendapat ATRA 10 mg/kgBB maupun kelompok kontrol.